Suprapatellar nail removal after suprapatellar nailing of the tibia: it could work! : Surgical technique and small case series - Branca Vergano, Luigi; Florio, Enrico Francesco; Prezioso, Vito; Monesi, Mauro; Landi, Stefano (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Intramedullary nailing is a fundamental tool for the treatment of meta-diaphyseal tibia fractures. While, in the past, the infrapatellar approach was the only one available, over the last few years, an alternative approach has been developed: the suprapatellar tibial nailing. This technique has shown some advantages over the other one. However, as the most recent method has become increasingly more common, concerns have been put forward about the possibility to remove the nail using only the infrapatellar approach, thus incising the previously unviolated patellar tendon. The aim of our study is to describe the technique and the results of a suprapatellar approach to remove the nail.Methods: We describe the surgical technique used to remove the tibial nail via the suprapatellar approach. We analyze a small case series of 12 patients who underwent the operation of nail removal, analyzing operation time, intraoperative and/or postoperative complications and clinical outcomes.Results: The mean duration of the operation was 39.8 minutes. The difference between the two values of the Lysholm score (pre- and postoperative) in each patient was not statistically significant, ranging between -2 to +4 points. We did not observe any intraoperative or postoperative complications.Conclusions: After suprapatellar nailing of the tibia, it is possible to remove the nail using the same suprapatellar approach with a safe, easy and reproducible technique. The clinical results observed in our case series show excellent outcomes in terms of absence of complications and good functional knee score.